1954
DOI: 10.1021/j150519a005
|View full text |Cite
|
Sign up to set email alerts
|

A New Cell Design for Precision Conductimetry

Abstract: The design of a conductance cell intended for use with dilute non-aqueous solutions is described. The electrodes (bright platinum) are concentric cylinders with the lead to the outer electrode being a platinum tube which acts as an electrical shield for the lead to the inner electrode. Stray electrical paths are thus eliminated. The electrode assembly is mounted on a Teflon plug which is turned to a standard taper, so that the electrodes are interchangeable. Tests covering the resistance range 1000 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1957
1957
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…at this temperature, 6.5 x 11101 L -l , and suggest again that "CI" for KNHCH, lies between 3 and 4 A.…”
Section: Potassi~tm Methylamide or Amide ?mentioning
confidence: 56%
See 1 more Smart Citation
“…at this temperature, 6.5 x 11101 L -l , and suggest again that "CI" for KNHCH, lies between 3 and 4 A.…”
Section: Potassi~tm Methylamide or Amide ?mentioning
confidence: 56%
“…The design of the electrode system was based on the recomnlendations of Nichol and Fuoss (6). The pair of concentric platinum cylinders (I cm diameter x 2 cm long and 2 cm diameter x 3 cm long) was mounted vertically in the conductivity cell (see Fig.…”
Section: Conductivity Cell Resistance Was Measured With a Beckmanmentioning
confidence: 99%
“…(39). Nichol and Fuoss [43] found that the simpler Eqs. (39) and (40) were inadequate to represent their data for dipping electrode designs and used this quadratic function of t ' .…”
Section: Resultsmentioning
confidence: 99%
“…B. FOLIC ACID COENZYMES A number of investigators (172)(173)(174)(175)(176)(177)(178)(179)(180)(181) have studied the conversion of folic acid by various in vivo and in vitro systems. In the cell-free extracts from mammalian, avian, and microbial sources, it was possible to demonstrate a requirement for: ( I ) formate, or a source of formate (eg., serine) ; and (2) a reducing agent, such as ascorbic acid or homocysteine.…”
Section: Biosynthesis Of Folic Acid and Its Coenzymes (1920)mentioning
confidence: 99%
“…The demonstration of the in vivo conversion of folic to folinic acid (172)(173)(174)(175)(176)(177)(178)(179)(180)(181)188), and the fact that Aminopterin toxicity was reversed far more effectively by folinic than by folk acid (9,188), led to the tentative identification of folinic acid as "active formate." However, it was not altogether clear how the folic acid-dependent transformations a t the oxidation level of formaldehyde fitted into the developing picture of tetrahydrofolic acid as the "coenzyme of transformylation."…”
Section: A T H E Role Of Folic Acid Coenzymes I N Intermediary Metabmentioning
confidence: 99%